2016
DOI: 10.1021/acsenergylett.6b00514
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tin Chloride in Tin-Rich Mixed-Halide Perovskites Applied as Mesoscopic Solar Cells with a Carbon Counter Electrode

Abstract: We report the synthesis and characterization of alloyed Sn–Pb methylammonium mixed-halide perovskites (CH3NH3Sn y Pb1–y I3–x Cl x ) to extend light harvesting toward the near-infrared region for carbon-based mesoscopic solar cells free of organic hole-transport layers. The proportions of Sn in perovskites are well-controlled by mixing tin chloride (SnCl2) and lead iodide (PbI2) in varied stoichiometric ratios (y = 0–1). SnCl2 plays a key role in modifying the lattice structure of the perovskite, showing anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 30 publications
1
55
0
Order By: Relevance
“…The “bowing” of the E g ( x ) dependence may originate from a transition from cubic to orthorhombic lattice symmetry upon increasing tin content [93]. A similar anomalous variation of the bandgap, as well as the CB/VB level positions with the Sn content, was reported for CH 3 NH 3 Sn x Pb 1− x I 3− y Cl y HPs [94]. …”
Section: Reviewmentioning
confidence: 64%
“…The “bowing” of the E g ( x ) dependence may originate from a transition from cubic to orthorhombic lattice symmetry upon increasing tin content [93]. A similar anomalous variation of the bandgap, as well as the CB/VB level positions with the Sn content, was reported for CH 3 NH 3 Sn x Pb 1− x I 3− y Cl y HPs [94]. …”
Section: Reviewmentioning
confidence: 64%
“…Hatton and co‐workers also reported the first demonstration of solution processed CsSnI 3 films at room temperature with much lower defect densities. However, the stability of these devices was relatively poor, with a 30% loss of PCE when stored in the dark and ambient air for only 1 h. To solve this problem, they further investigated the influence of SnX 2 (X = F, Cl, Br, and I) as additives as they have shown promising effects to enhance the resistance of oxidation toward air by other researchers . Among these, SnCl 2 outstands as being a particularly beneficial additive.…”
Section: Inorganic Perovskite Materials and Solar Cellsmentioning
confidence: 99%
“…It has been reported that SnF 2 additives in pure Sn perovskites reduce background carrier density, smooth the film surface, and increase carrier lifetimes . In mixed Sn‐Pb perovskites, the function of SnF 2 was found to increase current density and reduce hysteresis in low‐bandgap PSCs . Jen and co‐workers reported that SnF 2 additive in MAPb 0.5 Sn 0.5 I 3 perovskites improves the film quality without changing the bandgap .…”
Section: The Status Of Mixed Sn‐pb Pscsmentioning
confidence: 99%
“…Further increasing SnF 2 to over 20% results in the excessive SnF 2 residues, which is detrimental to device performance . Tsai et al reported that adding 30 mol% SnF 2 to MASn y Pb 1− y I 3− x Cl x precursor significantly increased the efficiency of the resulting PSCs from 2.15% to 4.35% and reduced the J–V hysteresis . Zong et al reported that SnF 2 ·3FACl additive in FACs‐based Sn‐Pb perovskite could improve the device efficiency and stability through grain boundary passivation .…”
Section: The Status Of Mixed Sn‐pb Pscsmentioning
confidence: 99%